Mortality of inhabitants in an area polluted by cadmium: 15 year follow up. Issue 3 (March 1995) - Nishijo, M; Nakagawa, H; Morikawa, Y; Tabata, M; Senma, M; Miura, K; Takahara, H; Kawano, S; Nishi, M; Mizukoshi, K
Abstract : OBJECTIVE–To assess the influence of environmental exposure to cadmium (Cd) on long term outcome of inhabitants living in an area polluted by Cd. METHODS–A follow up study for 15 years (from 1974-5 to 1991) was carried out on 2408 inhabitants (amounting to 95% of the target population, 1079 men and 1329 women) of the Kakehashi River basin in Ishikawa Prefecture, Japan. These inhabitants had been the subjects of the health impact survey in 1974-5 to evaluate (by measurement of urinary retinol binding protein (RBP)) renal dysfunction induced by Cd. Analysis of mortality was performed by dividing subjects into a urinary RBP positive (> or = 4 mg/l) group and RBP negative (< 4 mg/l) group. RESULTS–After adjustment for age with Cox's proportional hazard model, RBP > or = 4 mg/l showed a significant relation to mortality in both sexes. At this time, the mortality risk ratio of the RBP positive to negative group was 1.71 in the men and 1.42 in the women. When the SMRs according to causes of deaths in the RBP positive group were compared with those of the RBP negative group or the overall Japanese population increases of SMR for cardiovascular diseases, especially heart failure, and renal diseases were found in both sexes. CONCLUSION–These results suggest that the prognosis of the exposed inhabitants with renal tubular dysfunction is unfavourable, and these increases of mortality are due to heart failure and renal diseases.